Cases on teacher identity, diversity, and cognition in higher education - Breen, Paul, 1971- (A volume in the advances in higher education and professional development (AHEPD)book series, 2014)
"This thought-provoking collection of cases covers a range of educational contexts from preschool teaching in Europe to higher education in Australia and North America, and draws on expert knowledge of these diverse contexts, centered on a common theme of teacher identity"--